APB online workshop series: English for university professionals / Nur Ilianis Adnan - Adnan, Nur Ilianis (Academy of Language Studies, 2022)
APB Online Workshop Series 4: Giving Constructive Feedback which was held on 11th February 2022 marks the end of the online workshop series initiated by the Academy of Language Studies, UiTM Cawangan Pulau Pinang. The first three of its series entitled ‘Writing Error-Free Social Media Posts’, ‘Small talk’ and ‘Delivering Effective Speeches’ were conducted on 19th November 2021, 17th December 2021, and 14th January 2022 respectively. Series 4 was led by Dr. Nur Ilianis Adnan and the facilitators involved were Pn. Noor Laili Mohd Yusof, Pn. Aileen Farida Mohd Adam, Pn. Suzana Ab. Rahim, Pn. Farina Nozakiah Tazijan and Ms. Emily Jothee Mathai. The session was conducted for 2 hours, which started at 3 p.m. and ended at 5 p.m. via Google Meet. Lecturers and administrative staff from various faculties and departments participated in the series of workshops. Around 36 participants were involved, and they were divided into small groups of 6 to provide an opportunity for them to express their opinions, add ideas and ask questions. Small groups also encourage participants to know each other better, breaking down barriers and creating a more positive sharing atmosphere. Series 4 workshop was divided into 6 small segments. The first segment for icebreaking took around 10 minutes. This segment was crucial as it helped participants to get to know one another and create a nice atmosphere. The following 20 minutes had the facilitators taking the opportunity to give a brief introduction about the workshop. Then, the sharing session began. Slides and some pages of the book were shared on the google meet screen. A few TikTok videos related to giving feedback were also shared with the participants and one of the memorable formulas on giving feedback taken from the video was ‘love sandwich’ formula feedback. It is a way of giving feedback that goes like this: say something nice; then say the critical feedback - what you actually want to say; then say something nice again. After the sharing session, the participants were given 2 interactive and fun activities which required them to prepare, present and give/accept feedback from the other participants. Lastly, the facilitators wrapped up the session by summarizing the highlights of the workshop, thanking the participants for their active participation, and taking group photos. From the responses from the pre- and post- survey distributed to the participants, it was found that the participants had gained a lot of insights on how to give constructive feedback.